Rural Transformation and Poverty Reduction in Rural Area - Ahmad Saifullah Kamaludin (P4W LPPM IPB, 2023)
Rural Development is a major concern of the Indonesian government and has grown rapidly in the last decade. However, the pattern of development and its correlation to poverty remains a question mark. Using the Difference in Difference estimation model we analyzed whether the economic transformation in the rural area that occurred in the period 2014 to 2018 correlated with a decline in rural poverty. This study utilized secondary data from the micro dataset referring to the smallest administrative level named Village Potential from the Central Bureau of Statistics in Indonesia. Disaggregated by the transformed sectors, this study shows that the strongest correlation to the decline in the number of rural poor occurs when agricultural dominant-based villages have been complemented by adequate or have transformed as well to the service sector and other sectors. While the transformation to the trade sector shows the right direction of the correlation that reflects the decline in the number of poor people, the effect is still not significant. Atypical result in the transportation sector and industrial sector has not reduced poverty.